Slag system for electroslag remelting of low-Si low-Al martensitic heat-resistant steel containing B and Zr and smelting method

By using a specific proportion of slag system during the electroslag remelting process, the content and proportion of B2O3 and ZrO2 are controlled, the problem of burning of Zr and B elements is solved, and the quality stability of the electroslag ingot and B and Zr are improved. Receiving rate.

CN119410903AActive Publication Date: 2025-02-11CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411509643.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

During the electroslag remelting process, the Zr and B elements of low Si, low Al, B, and Zr martensite heat-resistant steels with low Si, low Al, B, Zr, are easily burned due to reaction with high Al2O3 slag, resulting in a decrease in yield and poor quality of the electroslag ingot. Stablize.

Method used

A specific slag ratio is adopted, including CaF2, Al2O3, CaO, MgO, B2O3 and ZrO2, and by controlling the content and proportion of B2O3 and ZrO2, it satisfies 2.0

Benefits of technology

The yield of B and Zr in the electroslag ingot is effectively improved, ensuring that its content is within the target range, and improving the quality stability and surface quality of the electroslag ingot.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105079550000071
    Figure BDA0005105079550000071
  • Figure BDA0005105079550000141
    Figure BDA0005105079550000141
Patent Text Reader

Abstract

The invention relates to a slag system for electroslag remelting of low-Si low-Al martensitic heat-resistant steel containing B and Zr and a smelting method, and belongs to the technical field of special metallurgy. The slag system comprises the following components in percentage by weight: 45-65% of CaF2; 11 to 20 percent of Al2O3; 15 to 27% of CaO; 2 to 5 percent of MgO; 0.5 to 5.0 percent of B2O3; zrO2: 2%-7%; b2O3 and ZrO2 in a slag system meet the condition that 1g ((% ZrO2) 3 / (% B2O3) 2) is more than 2.0 and less than 2.7. The content of B and Zr in the steel is controlled through the reaction of B and Zr dissolved in the molten steel and B2O3 and ZrO2 in the slag, namely 4 [B] + 3 (ZrO2) = 3 [Zr] + 2 (B2O3), so that the content of B and Zr in the steel is in a target range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special metallurgy, and in particular to a slag system for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel and a smelting method. Background Art

[0002] The development direction of martensitic heat-resistant steel is high strength, high toughness, good heat resistance and thermal fatigue resistance, etc., to meet the requirements of high temperature, high pressure, and long-term stable operation. In recent years, the composition design of advanced martensitic heat-resistant steel generally adopts low Si and low Al design. By controlling Si≤0.1% and Al≤0.015%, the precipitation of brittle Laves phase can be significantly delayed, toughness can be improved, and hot processing performance can be improved; at the same time, AlN formation is avoided, which consumes the solid solution strengthened N element and damages high temperature durability. In addition, the design of adding B and Zr to alloy elements has also become a trend. By actively adding 0.010-0.015% B and 0.005-0.02% Zr, the grain boundary strength can be improved and M can be suppressed. 23 C6 coarsening improves high temperature endurance performance; at the same time, Zr carbonitride reduces the tendency of grain growth, refines the grain size and improves toughness.

[0003] Si and Al are the most common deoxidizing elements in steel. However, for martensitic heat-resistant steel with Al content below 0.015% and Si content below 0.1%, the control of O content in the refining process poses a challenge. Martensitic heat-resistant steel is usually manufactured by electroslag remelting. For low-Si, low-Al and Zr-containing B martensitic heat-resistant steel, electroslag remelting can reduce the S content in the alloy, adsorb and remove large-sized inclusions, and significantly improve the forging performance of the steel ingot. Since Zr and B are both easily oxidized elements, the use of conventional slag systems containing high Al2O3 for remelting will cause burning due to the steel slag reaction: 3[Zr]+2(Al2O3)=4[Al]+3(ZrO2) or 2[B]+(Al2O3)=2[Al]+(B2O3), which greatly reduces the recovery rate of Zr and B and the quality stability of electroslag ingots, and at the same time leads to an increase in the Al content in the steel, exceeding the upper limit of the allowable composition. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a slag system and smelting method for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel to ensure the yield and quality of Zr and B in the electroslag ingot.

[0005] On the one hand, the present invention provides a slag system for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, which comprises, by mass percentage, CaF2: 45-65%; Al2O3: 11-20%; CaO: 15-27%; MgO: 2-5%; B2O3: 0.5-5.0%; ZrO2: 2-7%; SiO2≤0.5%; FeO≤0.7%, and B2O3 and ZrO2 in the slag system satisfy 2.0<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7. Wherein (%ZrO2) represents the mass percentage of ZrO2 in the slag, and (%B2O3) represents the mass percentage of B2O3 in the slag.

[0006] Furthermore, in terms of mass percentage, CaF2: 45-55%; Al2O3: 15-18%; CaO: 20-25%; MgO: 3-5%; B2O3: 0.5-3.0%; ZrO2: 3.0-6.0%; SiO2≤0.5%; FeO≤0.7%.

[0007] Furthermore, the melting temperature of the slag system is 1200-1350°C.

[0008] Furthermore, at 1500°C, the viscosity is ≤0.04 Pa·s, the conductivity is 1-2 / (Ω·cm), and the density is 2.90-3.10 g / cm 3 , the surface tension is 350~500mN / m.

[0009] On the other hand, the present invention provides a method for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, which uses the slag system of the present invention for smelting, comprising the following steps:

[0010] S1: Consumable electrode preparation: The surface of the consumable electrode rod should be fully polished, and there should be no iron oxide scale, shrinkage cavities, or scarring defects on the surface;

[0011] S2: Preparation of liquid slag: Use pre-prepared pre-melted slag, or mix CaF2, Al2O3, CaO, B2O3, MgO, and ZrO2 high-purity powders in proportion and melt them into liquid state. After smelting begins, add the liquid slag into the crystallizer in the form of arcing;

[0012] S3: Remelting: Use high-purity argon as a protective atmosphere for electroslag remelting, control the volume fraction of O2 in the atmosphere to be no higher than 0.02%, insert a consumable electrode rod into the crystallizer, add the liquid slag and start to energize at the same time;

[0013] S4: Shrinkage feeding: Before the end of remelting, the melting rate is reduced to feed shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot.

[0014] Furthermore, the chemical composition of the martensitic heat-resistant steel electroslag ingot, measured by mass percentage, includes: C: 0.08-0.15%; Si: ≤0.1%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.003%.

[0015] Further, in step S4, the filling ratio is 0.6 to 0.9.

[0016] Furthermore, the chemical composition of the consumable electrode rod, measured by mass percentage, includes: C: 0.08-0.14%; Si: ≤0.1%; Al: ≤0.012%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.0035%.

[0017] Furthermore, the melting rate of the remelting process is determined by the following formula:

[0018] v=(0.6~0.8)×D

[0019] Wherein, D is the diameter of the crystallizer, in mm; v is the melting rate, in kg / h.

[0020] Furthermore, in the martensitic heat-resistant steel electroslag ingot, lg([%Zr]×[%O] 2 )≤-7.4; wherein [%Zr] represents the mass percentage of Zr in the steel, and [%O] represents the mass percentage of O in the steel.

[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0022] 1. The present invention adds B2O3 to the slag, which can inhibit the burning of B in the steel through the slag-steel equilibrium reaction, improve the recovery rate of B in the steel, and ensure that the B content in the martensitic heat-resistant steel electroslag ingot is stably controlled at 0.010-0.017%;

[0023] 2. The present invention adds ZrO2 to the slag, which can inhibit the burning of Zr in the steel through the slag-steel balance, so that the Zr content in the martensitic heat-resistant steel electroslag ingot is within the target range; Zr: 0.005-0.02%;

[0024] 3. The present invention adds 0.5-5% B2O3 and 3-7% ZrO2 to the slag, and the contents of B2O3 and ZrO2 in the slag satisfy 2<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7, the B and Zr contents in the steel can be controlled by the reaction of B and Zr dissolved in the molten steel with B2O3 and ZrO2 in the slag 4[B]+3(ZrO2)=3[Zr]+2(B2O3), so that the B and Zr contents in the steel are within the target range;

[0025] 4. The melting temperature of the slag system of the present invention is in the range of 1200-1350°C, which is 100-200°C lower than the melting temperature of the martensitic heat-resistant steel, thereby preventing crystallization from occurring during the formation of the slag shell, and facilitating the formation of a thin slag shell to improve the surface quality of the steel ingot; the viscosity is ≤0.04Pa·s, which is conducive to the removal of inclusions, improving the cleanliness of the steel ingot, and providing good lubrication performance, which is conducive to the forming of the steel ingot;

[0026] 5. The present invention adopts the liquid slag arcing method to improve the uniformity of the slag, thereby improving the surface quality of the electroslag ingot. The melting rate of the electroslag remelting process is controlled to be v = (0.6-0.8) × D, which reduces the segregation of the alloy elements in the ingot, reduces the time for the floating removal of the metal molten pool inclusions, reduces the inclusion level of the electroslag ingot, and improves the cleanliness of the electroslag ingot.

[0027] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION

[0028] In order to meet the requirements of high temperature, high pressure, and long-term stable operation, martensitic heat-resistant steel needs to have high strength, high toughness, good heat resistance and thermal fatigue resistance, etc. At present, the above goals are mainly achieved through composition design. In the composition design process, low Si and low Al are used and B and Zr elements are added.

[0029] The low Si and low Al design can delay the precipitation of the brittle Laves phase, improve toughness, and improve hot working performance; at the same time, it can avoid the formation of AlN, consume the solid solution strengthening N element, and damage the high temperature durability. However, Si and Al are the most common deoxidizing elements in steel. For martensitic heat-resistant steels with low Si and Al contents, it is challenging to control the O content during the refining process.

[0030] Adding B and Zr elements can improve the grain boundary strength and inhibit M 23 The coarsening of C6 carbides improves high temperature durability. At the same time, the carbonitrides of Zr reduce the tendency of grain growth, refine the grain size, and improve toughness. However, B and Zr are easily oxidized elements, and their content is difficult to control.

[0031] In addition, the smelting process of martensitic heat-resistant steel adopts electric furnace melting plus external refining plus electroslag remelting or vacuum induction melting plus electroslag remelting. During the electroslag remelting process, the slag system contains a high content of Al2O3, which will react with B and Zr elements, 3[Zr]+2(Al2O3)=4[Al]+3(ZrO2) or 2[B]+(Al2O3)=2[Al]+(B2O3), causing burning, greatly reducing the recovery rate of Zr and B and the quality stability of electroslag ingots, and at the same time causing the Al content in the steel to increase, exceeding the upper limit of the allowable composition. Therefore, it is impossible to obtain martensitic heat-resistant steel with low Si and low Al, and B and Zr elements that meet the requirements.

[0032] Therefore, the present invention provides a slag system for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, which comprises, by mass percentage, CaF2: 45-65%; Al2O3: 11-20%; CaO: 15-27%; MgO: 2-5%; B2O3: 0.5-5.0%; ZrO2: 2-7%; SiO2≤0.5%; FeO≤0.7%, and B2O3 and ZrO2 in the slag system satisfy 2.0<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7.

[0033] Compared with the prior art, the present invention provides a slag system for electroslag remelting of low-Si, low-Al, B and Zr martensitic heat-resistant steel. According to the CaF2-CaO-Al2O3 ternary phase diagram, the CaF2-CaO-Al2O3 ratio of the basic components in the slag is obtained, and then a small amount of MgO is added to prevent oxygen from entering the air, and finally B2O3 and ZrO2 are added to balance with B and Zr in the steel. The designed slag system can inhibit the burning loss of B and Zr content in the steel and ensure the recovery rate of B and Zr.

[0034] The composite addition of B and Zr elements in martensitic heat-resistant steel can improve the grain boundary strengthening effect and obtain martensitic heat-resistant steel with higher performance, including:

[0035] B is an interstitial solid solution element. During the quenching process, it concentrates near the grain boundary and combines with the grain boundary vacancies to stabilize the grain boundary, thereby increasing the grain boundary strength. On the other hand, B atoms enter the grain boundary of heat-resistant steel and the M precipitated near the grain boundary. 23 In C6 carbide, M 23 (C 0.85 B 0.15 )6 carboboride, greatly delaying the M 23 However, when the B content is too high, BN inclusions will be formed, which will seriously deteriorate the thermal processing and welding properties of the material.

[0036] Zr segregates to the grain boundary, which can reduce grain boundary defects, improve grain boundary bonding, reduce grain boundary diffusion rate, slow down dislocation climb, and strengthen grain boundaries. Zr-containing carbonitrides can inhibit the growth of austenite grains, refine grain size, and improve the short-term strength and toughness of steel. However, Zr has a strong affinity with oxygen. When Zr combines with oxygen to form large-sized ZrO2 inclusions, microcracks will occur, which is detrimental to strength and toughness and damages the fatigue resistance of the material. Moreover, after Zr is added to the molten steel, it reacts with O to form ZrO2, which will cause nozzle nodules and affect castability.

[0037] Therefore, it is proposed to add a small amount of B2O3 and ZrO2 to the CaF2-CaO-Al2O3 basic slag system to control the B and Zr content in the steel. The functions of each component in the slag are as follows:

[0038] CaF2 is used to reduce the melting temperature, viscosity and surface tension of slag, which is beneficial to the dissolution of inclusions in the slag and improves the internal and surface quality of the ingot. When the CaF2 content is too high, the smelting process will volatilize seriously, resulting in excessive changes in the slag composition, which is not conducive to the stable control of the composition of large electroslag ingots and causes serious pollution. Therefore, the CaF2 content is controlled to be 45-65%.

[0039] CaO is used to increase the basicity of slag, reduce electrical conductivity and improve desulfurization efficiency. When the CaO content is too high, it will cause the melting point of the slag to increase, so the CaO content is controlled to 15-27%.

[0040] On the one hand, Al2O3 is used to reduce the conductivity of the slag, and on the other hand, it can also balance with the dissolved Al in the steel to control the Al content in the steel. When the Al2O3 content in the slag is too high, it will cause the steel slag to react, causing the Zr element to burn out, and the Al content will increase, exceeding the composition range. At the same time, Al2O3 will increase the melting point and viscosity of the slag, so the Al2O3 content is controlled to be 11-20%.

[0041] MgO can form a semi-solid film in the slag pool, reducing the oxygen, hydrogen and heat radiation of the slag surface to the atmosphere. When the MgO content is too high, it will affect the melting point and viscosity characteristics of the slag, as well as the crystallization characteristics of the slag, so the MgO content is controlled to be 2-5%. FeO in the slag is inevitable and will transfer O to the molten steel, so it is controlled as low as possible.

[0042] B2O3 and ZrO2 are used to precisely control the composition of electroslag ingots and improve the purity and composition uniformity of electroslag ingots. The addition of B2O3 and a small amount of ZrO2 helps to reduce the melting temperature of the slag and improve the surface quality. At the same time, B and Zr will react with the corresponding oxides in the slag through equations 1 to 6, so the contents of B2O3 and ZrO2 in the slag are controlled to be 0.5-5% and 2-7% respectively, and satisfy 2<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7, ensuring that both elements are within the control range at the same time.

[0043]

[0044] In addition, there will be a small amount of SiO2 and FeO brought into the slag from the raw materials, which will aggravate the burning loss of elements such as B and Zr. Their content should be reduced as much as possible, and SiO2 should be controlled to ≤0.5% and FeO ≤0.7%.

[0045] Specifically, by mass percentage, CaF2: 45-55%; Al2O3: 15-18%; CaO: 20-25%; MgO: 3-5%; B2O3: 0.5-3.0%; ZrO2: 3.0-6.0%; SiO2≤0.5%; FeO≤0.7%.

[0046] Specifically, the melting temperature of the slag system is 1200-1350°C.

[0047] Specifically, at 1500°C, the viscosity is ≤0.04 Pa·s, the conductivity is 1-2 / (Ω·cm), and the density is 2.90-3.10 g / cm 3 , the surface tension is 350~500mN / m.

[0048] It should be noted that the melting temperature of the slag system of the present invention is 100-200°C lower than the melting temperature of the martensitic heat-resistant steel, and the viscosity of the liquid slag after complete melting is low, which is conducive to forming a thin slag shell and improving the surface quality of the electroslag ingot. When the conductivity is too low, the electrode gap will be too small, causing the molten droplet to short-circuit and reducing the stability of the smelting process. When the conductivity is too high, the heat loss will increase significantly, which is not conducive to the smelting of the electrode.

[0049] In addition, the smaller the surface tension of the liquid slag, the smaller the adhesion work between the slag and the steel, the easier it is for the slag skin to fall off the surface of the steel ingot, and the liquid slag has a smaller effect on the adsorption and removal of inclusions. The density of the liquid slag will affect the flow of the molten metal. When the slag density is high, the flow of the liquid slag is restricted, the heat transfer efficiency is reduced, and the metallurgical reaction efficiency is reduced; when the density of the liquid slag is too low, it may cause increased fluctuations in the molten pool, too fast flow of the liquid slag, and too thin or uneven slag shell, thus affecting the surface quality and internal structure of the electroslag ingot.

[0050] By adopting the slag system ratio, the corresponding physical property parameters are helpful to improve the metallurgical properties of liquid slag in the electroslag remelting process, improve the purity of electroslag ingots, and improve the surface quality of electroslag ingots.

[0051] The present invention provides a method for electroslag remelting of a low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, which uses the slag system of the present invention for smelting, comprising the following steps:

[0052] S1: Preparation of consumable electrode: The surface of the consumable electrode rod should be fully polished, and there should be no iron oxide scale, shrinkage cavities, or scarring defects on the surface, and oxygenation or the introduction of large-sized foreign inclusions should be avoided;

[0053] S2: Preparation of liquid slag: Use pre-prepared pre-melted slag, or mix CaF2, Al2O3, CaO, B2O3, MgO, and ZrO2 high-purity powders in proportion, and use a medium-frequency induction furnace to completely melt them into liquid state. After the smelting starts, add the liquid slag to the crystallizer in the form of arcing;

[0054] S3: Remelting: Use high-purity argon as the protective atmosphere for electroslag remelting, control the O2 volume fraction in the atmosphere to be no higher than 0.02%, insert the consumable electrode rod into the crystallizer, and start powering on while adding liquid slag; the melting rate of the remelting process is determined by the following formula:

[0055] v=(0.6~0.8)×D

[0056] Wherein, D represents the diameter of the crystallizer, in mm; v represents the melting rate, in kg / h;

[0057] S4: Shrinkage feeding: Before the end of remelting, the melting rate is reduced to feed shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot.

[0058] Compared with the prior art, the slag system designed in the present invention has excellent metallurgical properties, which can improve the surface quality of the electroslag ingot during the smelting process and improve the cleanliness of the electroslag ingot. In addition, adding a small amount of B2O3 and ZrO2 to the slag can balance with B and Zr in the steel, thereby controlling the B and Zr content in the steel so that the B and Zr content reach the target range. The use of pre-melted slag in the remelting process ensures uniform slag composition, which is beneficial to improving the uniformity of the ingot composition. Baking the slag before smelting ensures the internal quality of the electroslag ingot and avoids defects such as holes.

[0059] Specifically, the chemical composition of the consumable electrode rod, by weight percentage, includes C: 0.08-0.14%; Si: ≤0.1%; Al: ≤0.012%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.0035%.

[0060] It should be noted that in order to avoid the increase of Al in the electroslag remelting process due to the addition of Zr elements, the Al content in the consumable electrode rod is required to be appropriately reduced.

[0061] Specifically, the chemical composition of the martensitic heat-resistant steel electroslag ingot, by weight percentage, includes: C: 0.08-0.14%; Si: ≤0.1%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.003%. And satisfying lg([%Zr]×[%O] 2 )≤-7.4, to avoid the formation of a large number of large-sized ZrO2 inclusions that deteriorate the performance of martensitic heat-resistant steel electroslag ingots.

[0062] It should be noted that during the smelting stage, the low Si, low Al, B and Zr containing composition design has a higher smelting difficulty, especially in the electroslag remelting stage, it is very easy to increase Al, resulting in excessive Al content, and B and Zr are easily burned through slag-steel reaction, resulting in fluctuations in the beginning and end yields.

[0063] Specifically, in step S4, the filling ratio is 0.6-0.9, and the melting rate v=(0.6-0.8)×D.

[0064] It should be noted that the filling ratio refers to the ratio of the consumable electrode to the diameter of the crystallizer; a filling ratio that is too high will lead to a decrease in the slag refining effect and reduce the cleanliness of the steel, while a filling ratio that is too low will increase the depth of the molten pool, reduce the efficiency of inclusion removal and reduce production efficiency. This melting rate is the melting rate of the optimized martensitic heat-resistant steel electroslag ingot. The electroslag ingot prepared at this melting rate has good surface quality and a low risk of internal quality defects.

[0065] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0066] Example 1

[0067] A method for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, using the slag system of the present invention for smelting, comprises the following steps:

[0068] S1: Preparation of consumable electrode: The surface of the consumable electrode rod should be fully polished, and there should be no iron oxide scale, shrinkage cavities, or scarring defects on the surface, and oxygenation or the introduction of large-sized foreign inclusions should be avoided;

[0069] The chemical composition of the consumable electrode rod is C: 0.12%; Si: 0.08%; Al: 0.01%; Mn: 0.50%; Cr: 9.0%; W: 2.1%; Mo: 0.48%; Co: 3.0%; V: 0.2%; Nb: 0.05%; Zr: 0.018%; B: 0.015%; N: 0.008%; O: 0.003%;

[0070] S2: Preparation of liquid slag: 48.3% CaF2, 17% Al2O3, 23% CaO, 5% MgO, 0.9% B2O3 and 5.2% ZrO2 are mixed and completely melted into liquid state by medium frequency induction furnace. After smelting begins, the liquid slag is added into the crystallizer in the form of arcing; lg((% ZrO2) 3 / (%B2O3) 2 )=2.24;

[0071] S3: Remelting: Use high-purity argon as the protective atmosphere for electroslag remelting, control the O2 volume fraction in the atmosphere to be no higher than 0.02%, insert the consumable electrode rod into the crystallizer, and start powering on while adding liquid slag; the melting rate v during the remelting process is 0.7×D;

[0072] S4: Feeding: Before the end of remelting, the melting rate is reduced to feed the shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot;

[0073] The melting temperature of the slag system is 1289℃, and the electrical conductivity of the slag system is 1.72 / (Ω·cm) at 1500℃. -1 , viscosity is 0.035Pa·s, surface tension is 475.83N / m;

[0074] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0140%, the Zr content is 0.0181%, the Al content is 0.010%, and the O content is 0.001%. lg([%Zr]×[%O] 2 )=-7.74<-7.4. Yield: B: 93.3%, Al: 100%, Zr: 100%. Class B inclusions: 0.5 level.

[0075] Example 2

[0076] The preparation process of Example 2 is substantially the same as that of Example 1, except that the chemical composition mass percentage of the slag system used in Example 2 is 54.0% CaF2, 17.8% Al2O3, 20.1% CaO, 3.0% MgO, 0.5% B2O3 and 4.5% ZrO2 and inevitable impurities, wherein the SiO2 content of the impurities is 0.38% and the FeO content is 0.28%; lg((% ZrO2) 3 / (%B2O3) 2 )=2.56;

[0077] The melting temperature of the slag system is 1344℃, and the electrical conductivity of the slag system is 1.75 / (Ω·cm) at 1500℃. -1 , viscosity is 0.024Pa·s, surface tension is 429.99N / m;

[0078] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0110%, the Zr content is 0.0165%, the Al content is 0.011%, and the O content is 0.0015%. lg([%Zr]×[%O] 2 )=-7.44<-7.4. Yield: B: 73.3%, Al: 110%, Zr: 91.7%. Class B inclusions 0.5 level.

[0079] Comparative Example 1

[0080] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that the chemical composition mass percentage of the slag system used in Comparative Example 1 is 49.9% CaF2, 17.6% Al2O3, 23.5% CaO, 2.8% MgO, 4.2% B2O3 and 1% ZrO2 and inevitable impurities, wherein the SiO2 content of the impurities is 0.43% and the FeO content is 0.37%; lg((% ZrO2) 3 / (%B2O3) 2 )=-1.25;

[0081] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0400%, the Zr content is 0.0023%, the Al content is 0.013%, and the O content is 0.0030%. lg([%Zr]×[%O] 2 )=-7.68<-7.4. Yield: B: 267%, Al: 130%, Zr: 12.8%. Class B inclusions 0.5 level.

[0082] Comparative Example 2

[0083] The preparation process of Comparative Example 2 is substantially the same as that of Example 1, except that the chemical composition of the slag system used in Comparative Example 2 is 46.4% CaF2, 16.5% Al2O3, 24.0% CaO, 4.0% MgO, 0.3% B2O3 and 7.8% ZrO2 and inevitable impurities by mass percentage, and the SiO2 content of the impurities is 0.39%, and the FeO content is 0.26%. lg((% ZrO2) 3 / (%B2O3) 2 )=3.72;

[0084] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0040%, the Zr content is 0.0220%, the Al content is 0.010%, and the O content is 0.0015%. lg([%Zr]×[%O] 2 )=-7.30>-7.4. Yield: B: 22.2%, Al: 100%, Zr: 122%. Class B inclusions: 1.0.

[0085] Comparative Example 3

[0086] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that the chemical composition mass percentage of the slag system used in Comparative Example 3 is 52.3% CaF2, 17.8% Al2O3, 23.6% CaO, 5.0% MgO and inevitable impurities, and the SiO2 content in the impurities is 0.38%, and the FeO content is 0.30%;

[0087] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0039%, the Zr content is 0.0025%, the Al content is 0.014%, and the O content is 0.0030%. lg([%Zr]×[%O] 2 )=-7.64<-7.4. Yield: B: 26%, Al: 140%, Zr: 13.9%. Class B inclusions 0.5 level.

[0088] Comparative Example 4

[0089] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that the chemical composition mass percentage of the slag system used in Comparative Example 4 is 45.4% CaF2, 25.7% Al2O3, 20.8% CaO, 3.0% MgO, 0.5% B2O3 and 3.5% ZrO2 and inevitable impurities, and the SiO2 content of the impurities is 0.45%, and the FeO content is 0.33%. lg((% ZrO2) 3 / (%B2O3) 2 )=2.23;

[0090] The above slag system is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010-0.017%; Zr: 0.005-0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0080%, the Zr content is 0.0050%, and the Al content is 0.025%, which exceeds the composition range. The O content is 0.0025%. lg([%Zr]×[%O] 2 )=-7.51<-7.4. Yield: B: 53.3%, Al: 250%, Zr: 27.8%. Class B inclusions 0.5 level.

[0091] Comparative Example 5

[0092] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the melting rate used in Comparative Example 5 is v=0.85D.

[0093] The above process is used for electroslag remelting. The requirements for B and Zr content in the remelting steel are B: 0.010~0.017%; Zr: 0.005~0.02%. The specific remelting steps are shown in the above process. The steel ingot after remelting is sampled and analyzed. The B content in the steel is 0.0142% and the Zr content is 0.0185%. However, the ZrO2 inclusions in the steel exceed the standard, the Al content is 0.010%, and the O content is 0.0019%. lg([%Zr]×[%O] 2 )=-7.13>-7.4. Yield: B: 94.7%, Al: 100%, Zr: 102.8%. Class B inclusions: 1.0.

[0094] Ingredient testing

[0095] The above-mentioned Examples 1-2 and Comparative Examples 1-5 were subjected to component detection and inclusion detection, and the specific detection results are shown in Table 1.

[0096] Table 1 B, Zr and Al contents in steel after electroslag remelting

[0097]

[0098] Combining Examples 1-2 and Comparative Examples 1-5 with Table 1, it can be seen that the slag system provided by the present invention includes CaF2: 45-65%; Al2O3: 11-20%; CaO: 15-27%; MgO: 2-5%; B2O3: 0.5-5.0%; ZrO2: 2-7%; SiO2≤0.5%, FeO≤0.7%, and B2O3 and ZrO2 in the slag system satisfy 2.0<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7, the contents of B, Zr and Al in the obtained electroslag ingot all meet the requirements.

[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A slag system for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, characterized in that: In terms of mass percentage, it includes CaF2: 45-65%; Al2O3: 11-20%; CaO: 15-27%; MgO: 2-5%; B2O3: 0.5-5.0%; ZrO2: 2-7%; SiO2≤0.5%; FeO≤0.7%, and B2O3 and ZrO2 in the slag system satisfy 2.0<lg((%ZrO2) 3 / (%B2O3) 2 )<2.7; wherein (%ZrO2) represents the mass percentage of ZrO2 in the slag, and (%B2O3) represents the mass percentage of B2O3 in the slag.

2. The slag system for electroslag remelting of low Si, low Al, B and Zr-containing martensitic heat-resistant steel according to claim 1, characterized in that: In terms of mass percentage, CaF2: 45-55%; Al2O3: 15-18%; CaO: 20-25%; MgO: 3-5%; B2O3: 0.5-3.0%; ZrO2: 3.0-6.0%; SiO2≤0.5%; FeO≤0.7%.

3. The slag system for electroslag remelting of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 1 or 2, characterized in that: The melting temperature of the slag system is 1200-1350°C.

4. The slag system for electroslag remelting of low Si, low Al, B and Zr-containing martensitic heat-resistant steel according to claim 1, characterized in that: At 1500℃, the viscosity is ≤0.04Pa·s, the conductivity is 1~2 / (Ω·cm), and the density is 2.90~3.10g / cm 3 , the surface tension is 350~500mN / m.

5. A method for electroslag remelting of low-Si, low-Al, B- and Zr-containing martensitic heat-resistant steel, characterized in that: The smelting process using the slag system according to any one of claims 1 to 4 comprises the following steps: S1: Consumable electrode preparation: The surface of the consumable electrode rod should be fully polished, and there should be no iron oxide scale, shrinkage cavities, or scarring defects on the surface; S2: Preparation of liquid slag: Use pre-prepared pre-melted slag, or mix CaF2, Al2O3, CaO, B2O3, MgO, and ZrO2 high-purity powders in proportion and melt them into liquid state. After smelting begins, add the liquid slag into the crystallizer in the form of arcing; S3: Remelting: Use high-purity argon as a protective atmosphere for electroslag remelting, control the volume fraction of O2 in the atmosphere to be no higher than 0.02%, insert a consumable electrode rod into the crystallizer, add the liquid slag and start to energize at the same time; S4: Shrinkage feeding: Before the end of remelting, the melting rate is reduced to feed shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot.

6. The electroslag remelting method of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 5, characterized in that: The chemical composition of the martensitic heat-resistant steel electroslag ingot, measured by mass percentage, includes: C: 0.08-0.15%; Si: ≤0.1%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.003%.

7. The electroslag remelting method of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 5, characterized in that: In step S4, the filling ratio is 0.6 to 0.

9.

8. The electroslag remelting method of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 5, characterized in that: The chemical composition of the consumable electrode rod, measured by mass percentage, includes: C: 0.08-0.14%; Si: ≤0.1%; Al: ≤0.012%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; Zr: 0.005-0.02%; B: 0.010-0.017%; N: 0.006-0.014%; O: ≤0.0035%.

9. The electroslag remelting method of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 5, characterized in that: The melting rate of the remelting process is determined by the following formula: v=(0.6~0.8)×D Wherein, D is the diameter of the crystallizer, in mm; v is the melting rate, in kg / h.

10. The electroslag remelting method of low Si, low Al, B and Zr martensitic heat-resistant steel according to claim 5, characterized in that: The martensitic heat-resistant steel electroslag ingot contains lg ([% Zr] × [% O] 2 )≤-7.4; wherein [%Zr] represents the mass percentage of Zr in the steel, and [%O] represents the mass percentage of O in the steel.

Citation Information

Patent Citations

  • Heat resistant steel for ultra-supercritical castings at 650 DEG C

    CN105695881A

  • Slag system for electroslag remelting of B-containing type 9Cr heat resistant steel, preparation method and using method

    CN110453085A

  • Heat-resistant steel for ultra-supercritical steam turbine rotor forge piece and preparation method of heat-resistant steel

    CN114622133A

  • Martensite heat-resistant steel as well as preparation method and application thereof

    CN116716545A

  • Austenitic heat-resistant steel for air valve and preparation method thereof

    CN118127425A